Nanotechnology for fungal pathogen control in crops: innovations, public health impacts, and disease prevention - Ogwu, Matthew Chidozie; Izah, Sylvester Chibueze (Frontiers in Fungal Biology, 2025)
Fungal pathogens continue to devastate global agriculture, causing significant crop losses, compromising food security, and posing emerging threats to public health. This paper critically examines the revolutionary role of nanotechnology-driven innovations in combating fungal diseases in crops, offering an integrative framework that bridges plant health, environmental sustainability, and human well-being. We synthesize recent advancements in agricultural nanomaterials, including silver, zinc oxide, and copper oxide nanoparticles, as well as green-synthesized nanoformulations. We examine their antifungal mechanisms, including membrane disruption, induction of oxidative stress, targeted delivery, and inhibition of spore germination. The review highlights how nanosensors can facilitate early detection of pathogens, while nano-enabled packaging and innovative delivery systems prevent post-harvest contamination and extend shelf life. Crucially, we underscore the public health benefits of reduced chemical pesticide use, lowered mycotoxin exposure, and the potential for mitigating antimicrobial resistance. The paper advances the discourse on environmentally responsible, high-precision disease control strategies in agriculture by linking nanotechnology to broader sustainability goals. Furthermore, we identify key challenges, including regulatory ambiguity, ecotoxicological concerns, and barriers to equitable adoption, especially among smallholder farmers in the Global South. This paper contributes a forward-looking agenda for integrating nanotechnology into holistic pest management systems through inclusive policies, interdisciplinary research, and stakeholder-driven implementation pathways. Overall, this review positions nanotechnology as a transformative tool in reengineering crop protection paradigms that align innovation with sustainability, resilience, and public health imperatives in the face of escalating global challenges.